Analisis Mekanisme Arum Pembiayaan Haji dalam Pegadaian Syariah - M.Aziz Zakiruddin (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2019)
Pawn is a business activity that may be commonplace we find in the community environment, the need requires us to get a funding, so the lien is an alternative, to get the funds. PT Pegadaian Syariah is large pawn institutions and provide superior products, one of Arum Haji, Arum Haji one of the alternativ of people who want to Hajj, but not have enough funds, so pawnshops, providing financing to perform the pilgrimage, by way of, customers pawned gold weighing 15 grams or worth 7 million rupiah. By plucking the gold, the customer will get the financing in the form of Hajj savings worth 25 million rupiah, this is enough to attract the community and lifted the enthusiasm of the community, the convenience of this pawnshop attracts the author to do the analysis, the calculation mechanism in Arum Haji, if we see from the mechanism of calculating the mortgage on generally. if we look through the mechanism of calculation in pawnshops then we will find a point question, how the gold weighs 15 grams in the appraiser for 32 million rupiah, while if we see from the mechanism of calculating mortgage, gold weighing 15 grams, the possibility of funds that can lend amounting to 7 million - 8 million rupiahs, how the pawnshops make an appraisal of gold on Arum Haji products, so he gives a high estimate of 15 grams of gold, and provide a loan of 25 million is sufficient to register and get the portion number of pilgrims.  Looking at the calculation mechanism the authors did not find the exact calculation formula, which is used in Arum Hajj, so the authors assume, it is a marketing method to attract customers to pawn in PT Pegadaian sharia, and speculation alone, which assumes gold price will one day reach at a high price point, and then the loan is given to the customer who has the ability to return high enough, so it will not happen its one achievement. Keyword : Pawn, Pawnshop, Islamic Pawnshop, Arum Haji.